Territorial and political mobility in the speech of indigenous leaders of/in the State of Acre (Amazonia, Brasil) (Terr@ Plural, 2020)
It is proposed to discuss territorial mobility, the policies of indigenous leaders in the state of Acre, especially the Manchineri, their survival strategies in the world of non-indigenous people so that we can reflect on two changes that we testify in recent decades: mobility for the urban centers that include the indigenous people who were born in the city and those who arrived in the city, as well as its growing support in the country’s indigenous and non-indigenous political discussions in Brazil. The methodological path had as its own perspective of the leaders, for this will be reported their way of life and their involvement in the policies of different spheres of decision. The paper consists of three discussion sections that go from mobility to the political role played by leaders.
Keywords: Indigenous Peoples; indigenous policies; strategies and protagonisms